Disposable : America's contempt for the underclass - Jones, Sarah, 1988- (Avid Reader Press, 2025)
A powerful blend of narrative and reporting reveals America's systemic racial and income inequality, spotlighting essential workers and vulnerable communities disproportionately impacted by COVID-19 and argues for a future where no one is deemed disposable amid persistent social injustices.